TEACHING READING COMPREHENSION AND WRITING SKILL THROUGH SCAFFOLDED READING EXPERIENCE STRATEGY TO THE EIGHTH GRADE STUDENTS OF SMP NEGERI 53 PALEMBANG - Rahmita Dwi Lestari (ELTE Journal (English Languange Teaching and Education), 2013)
AbstractThis study was meant to reaveal the teaching reading comprehension and writing skill through scaffolded reading experience strategy of the eight grade students of SMP Negeri 53 Palembang, including to find whether or not (1) there wassignificant differences in students’ reading comprehension achievements before and after they are taught by using scaffolded reading experience strategy, (2) there was significant differences in students’ writing achievements before and after they are taught by using scaffolded reading experience strategy, (3) there were significant difference in students’ reading comprehension achievements betweenexperimental and control group, (4) there were significant difference in students’ writing achievements between experimental and control group, and (5) how muchis the contribution of SRE to students’ reading achievement and students’ writing achievement of the eight grade students of SMP Negeri 53 Palembang. The population of the study was the eight grade students of SMP Negeri 53 Palembangin the academic year 2012-2013 consisting of 208 students. From population, 60 students were taken as her research sample. 30 students represented in an experimental group and the rest of them were in control group. The quantitativeresearch was used as the approach of this study. In carrying out this research, a cluster random sampling was used. From the finding of the research, it can be concluded that: (a) there was a significant difference in students’ reading comprehension achievement before and after they were taught by using SRE. It means that (Ho) is rejected and (Ha) is accepted; (b) there was a significantdifference in students’ writing achievement before and after they were taught by using SRE. It means that (Ho) is rejected and (Ha) is accepted; (c) there was a significant difference in students’ reading comprehension achievement betweenexperimental and control group. It means that (Ho) is rejected and (Ha) is accepted; (d) there was a significant difference in students’ writing achievement between experimental and control group. It means that (Ho) is accepted and (Ha) is rejected; and (e) SRE could give a contribution on students’ reading achievement and writing achievement. It means that (Ho) is accepted and (Ha) isrejected.Keywords: reading comprehension, writing skill, and scaffolded reading experience strategy.